Development and validity evidence on the scale of perceived social support for university students (EPSSEU) during the period of social restrictions - Bruno, Thaís Calcagno Vidon; Custódio, Isis Danyelle Dias; de Menezes-Junior, Luiz Antônio Alves; Meireles, Adriana Lúcia; Neves, Ana Cláudia Morito; Barroso, Sabrina Martins; Carraro, Júlia Cristina Cardoso (BMC public health, 2024)
This study aims to validate a Perceived Social Support Scale for University Students (EPSSEU) during periods of social restrictions, by focusing on family and university support. This cross-sectional study was conducted with undergraduate students from a public higher education institution. The college students who participated in the study-1353 at baseline and 378 after 6 months-answered a virtual questionnaire containing questions on: sociodemographic and lifestyle data, items proposed for the EPSSEU, Satisfaction with Social Support Scale (ESSS), and Depression, Anxiety and Stress Scale (DASS-21). Exploratory factor analysis, Cronbach's alpha reliability analysis, as well as discriminant, convergent, and known-group validations were performed. The results showed two factors support from: i) the university and ii) friends and family- which explained 61.82% of the variance in the data. The EPSSEU showed good reliability (Cronbach's alpha = 0.796) as well as validity, with higher scores among individuals without depression, anxiety, or stress. The EPSSEU shows adequate psychometric qualities and may be a useful instrument for assessing university students' social support in pandemics, social distancing, and remote teaching contexts.